2013
DOI: 10.3390/molecules18078257
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Activities of (−)-Anonaine

Abstract: Several species of Magnoliaceae and Annonaceae are used in Traditional Chinese Medicine. (−)-Anonaine, isolated from several species of Magnoliaceae and Annonaceae, presents antiplasmodial, antibacterial, antifungal, antioxidation, anticancer, antidepression, and vasorelaxant activity. This article provides an overview of the pharmacological functions of (−)-anonaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 28 publications
(53 reference statements)
1
21
0
1
Order By: Relevance
“…Important biological activities such as antioxidant, antimicrobial and different pharmacological effects in cardiovascular system, besides significant activity in central nervous system acting in depressive disorders are also reported for anonaine . Besides the antiplasmodial activity of anonaine to resistant chloroquine parasites, anonaine should be pointed out as a potential anticancer compound taking into account its cytotoxicity to HepG2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Important biological activities such as antioxidant, antimicrobial and different pharmacological effects in cardiovascular system, besides significant activity in central nervous system acting in depressive disorders are also reported for anonaine . Besides the antiplasmodial activity of anonaine to resistant chloroquine parasites, anonaine should be pointed out as a potential anticancer compound taking into account its cytotoxicity to HepG2.…”
Section: Resultsmentioning
confidence: 99%
“…Important biological activities such as antioxidant, antimicrobial and different pharmacological effects in cardiovascular system, besides significant activity in central nervous system acting in depressive disorders are also reported for anonaine. [34] Besides the antiplasmodial activity of anonaine to resistant chloroquine parasites, anonaine should be pointed out as a potential anticancer compound taking into account its cytotoxicity to HepG2. Indeed, it has been shown that anonaine induces apoptosis through Bax-and caspasedependent pathways in HeLa cells and might be considered a potent compound for chemotherapy against human cervical cancer, because of its effect killing specifically cancer cells, but being safe to normal cells.…”
Section: Identification Of the Alkaloids Isolatedmentioning
confidence: 99%
“…[40] The influence of season on phytochemical profile and thus bioactivity might be attributed to environments conditions as well as different phenology stages. [41] The low inhibitory activity of stems and leaves, which was null for extracts from some collections, would indicate that the tested fungi are quite resistant to the contained alkaloids or to the combination present in these organs. [37] Therefore, an inclusive analysis of environment and phenology is necessary to understand the modulation of secondary metabolism, with an alternative being the study of young plants wherein the phenological factors can be separated.…”
Section: Discussionmentioning
confidence: 99%
“…Anonaine has been reported to have strong antimicrobial activity. [41] The low inhibitory activity of stems and leaves, which was null for extracts from some collections, would indicate that the tested fungi are quite resistant to the contained alkaloids or to the combination present in these organs. This result shows the importance of the roots of this species in obtaining active molecules, as a consequence of the plant distribution of its chemical defenses.…”
Section: Seasonality and Foliar Phenologymentioning
confidence: 99%
“…Alcaloides deste tipo já foram descritos em folhas de A. crassiflora Tsai et al, 1989;Li et al, 2013;).…”
Section: Atividade Antimicrobianaunclassified